N-nitrosamines in drinking water and beer: Detection and risk assessment. (June 2018) - Fan, Chun-Cheng; Lin, Tsair-Fuh
Abstract: Occurrence and risk related to nitrosamines, a group of carcinogenic compounds found in some drinking waters and beer, are studied. An analytical method using a solid-phase micro-extraction (SPME) along with gas chromatography (GC) and mass spectrometry (MS) was developed to determine seven N -nitrosamines in drinking water and beer, including N -nitrosomethylamine (NMEA), N -nitrosodiethylamine (NDEA), N -nitrosodimethylamine (NDMA), N -nitrosodi- n -propylamine (NDPA), N -nitrosopyrrolidine (NPyr), N -nitrosopiperidine (NPip), and N -nitrosodinbutylamine (NDBA). The analysis can be completed in 70 min, and only a 4 mL sample is required, with a detection limit of 0.1–0.8 ng/L for the seven nitrosamines in water and 6–15.7 ng/L in beer. The method was applied to analyze water samples collected from 11 reservoirs and their associated drinking water treatment plants in Taiwan and 10 beer samples from 6 brands with factories located in 6 countries. In the drinking water samples, all seven N -nitrosamines were detected, with NDMA having the highest level at 10.2 ng/L. In the beer samples, NDMA was detected at much lower concentrations (0.12–0.23 μg/L) than the 5 μg/L US standard, while NPip was detected at much higher concentrations (4.1–5.3 μg/L) compared to NDMA. The risk assessment indicates that the risk associated with NDMA is the highest among the studied N -nitrosamines in Taiwan's drinking water, with an average cancer risk of 6.4 × 10 −06 . For other nitrosamines, the risks are all below 10 −6 . For the risks associated with N -nitrosamines in beer, NDMA, NDEA, NDPA, and NPip are in the range of 1.5 × 10 −05 to 4.6 × 10 −04, while that for other nitrosamines are much lower. As for beer, no information for NPip and no modern information for NDEA and NDPA have previously been available, more studies about nitrosamines in beer are suggested for better estimation and control of the risks associated with consumption of beer. Highlights: An HSSPME GCMS method was used to detect 7 nitrosamines in drinking water and beer. NDMA was found to have the highest level at 16.3 ng/L in drinking water samples. For the first time, NPip was detected at high concentrations (>3.8 μg/L) in beers. The risk of NDMA is the highest among the nitrosamines in Taiwan's drinking water. The risks of NDEA, NDPA, and NPip in beer are similar to that of NDMA.